SQ4R Approach To Improve The Ability Of Mathematical Connections And Adversity Quotient Matematik MTs Students - Tresnawati, Siti Nur (MEJ (Mathematics Education Journal), 2018)
This study is a quasi experiment, which aims to examine the achievementand improvement of mathematical connection ability and Adversity Quotientof Mts students through SQ4R learning as a whole and based on KAM andassociation among variables. The population in this research is all students ofclass VIII MTsN 1 Subang. Samples were taken by random class, which arefrom eight grade obtained two classes, namely VIII D as the experimentalclass and class VIII A as the control class. Instruments in this study wereeach set of tests for mathematical connections, and a set of student’sadversity quotient scales and a set of student’s scale of views on SQ4Rlearning. The study found that the achievement and improvement ofmathematical connection ability of students whose learning using SQ4Rlearning is better than that of learning using ordinary learning as a whole orreviewed from KAM. And also adversity quotient of students who studyusing SQ4R is better than the learning using ordinary learning. it was alsofound an association between the ability of connections and adversityquotient of students in the classroom using SQ4R learning. The student’sperformance illustration during the SQ4R study shows the student’s activityboth individually or in cooperate in their group to build new knowledge thatmust be owned by students, so that improving the ability of mathematicalconnections as well as the adversity quotient of the student.